Associations between Physical Exercise, Quality of Life, Psychological Symptoms and Treatment Side Effects in Early Breast Cancer. (19th November 2022) - Vehmanen, Leena; Mattson, Johanna; Karademas, Evangelos; Oliveira-Maia, Albino J.; Sousa, Berta; Pat-Horenczyk, Ruth; Mazzocco, Ketti; Simos, Panagiotis; Cardoso, Fátima; Pettini, Greta; Marzorati, Chiara; Kolokotroni, Eleni; et al.
Abstract : Background . Identifying and understanding modifiable factors for the well-being of cancer patients is critical in survivorship research. We studied variables associated with the exercise habits of breast cancer patients and investigated if the achievement of exercise recommendations was associated with enhanced quality of life and/or psychological well-being. Material and Methods . 311 women from Finland, Portugal, Israel, and Italy receiving adjuvant therapy for stage I–III breast cancer answered questions about sociodemographic factors and physical exercise. Quality of life was assessed by the EORTC C30 and BR23 questionnaires. Anxiety and depression were evaluated using the HADS scale. Results . At the beginning of adjuvant therapy and after twelve months, 32% and 26% of participants were physically inactive, 27% and 30% exercised between 30 and 150 minutes per week, while 41% and 45% exercised the recommended 150 minutes or more per week. Relative to other countries, Finnish participants were more likely to be active at baseline and at twelve months (89% vs. 50%, p < 0.001 and 87% vs. 64%, p < 0.001 ). Participants with stage I cancer were more likely to be active at twelve months than those with a higher stage (80% vs. 70%, p < 0.05 ). The inactive participants reported more anxiety (p < 0.05 ) and depression (p < 0.001 ), lower global quality of life (p < 0.001 ), and more side effects (p < 0.05 ) than the others at twelve months. Accordingly, those who remained inactive or decreased their level of exercise from baseline to twelve months reported more anxiety (p < 0.01 ) and depression (p < 0.001 ), lower global quality of life (p < 0.001 ), and more side effects (p < 0.05 ) than those with the same or increased level of exercise. Conclusion . For women with early breast cancer, exercise was associated with a better quality of life, less depression and anxiety, and fewer adverse events of adjuvant therapy. Trial registration number: NCT05095675 . Paula Poikonen-Saksela on behalf of Bounce consortium (https://www.bounce-project.eu/ ).